Detection of microorganisms and characterization of histopathological lesions in cultivated and wild scallops (Argopecten purpuratus) in summer and winter - Valera A., Adhemir (2023)
The aim of this study was to detect parasitic agents and describe histopathological lesions in scallops (Argopecten purpuratus) from Ancash, Peru, during the summer and winter periods. In total, 360 mollusks were collected, in equal parts from aquaculture farms and wildlife, and in the summer and winter seasons (90 per group). The samples were preserved in Davidson's solution and analyzed by histology. The Chi-square test was used to determine possible associations between the variables. The histopathological findings in digestive glands and gills were similar, finding intracellular microcolonies of bacteria (ICM), hemocyte infiltration and tissue necrosis in all study groups. The prevalence of MCI was associated with the season of the year. Nephridial concretions occurred in all groups. The mantle was mostly affected by the presence of trematodes and hemocyte infiltration, especially in summer. It is concluded that there are microorganisms that affect and cause tissue lesions in Peruvian scallops.